Does CEO Traits Influence Innovation? Evidence from the Kenya Banking Sector - Tuwey, Joel Kiplagat; Ngeno, Vincent (Journal of Accounting, Business and Finance Research, 2019)
Empirical research on firm innovation has provoked mixed reactions from various scholars in the recent past. The main purpose of this study is to determine the influence of CEO traits on innovation among financial institutions in Kenya on the basis of upper echelons and optimism theories. The study used the design of the explanatory survey. The survey data for 130 stratified financial firms were analysed using both descriptive and inferential statistics. Regression analysis was used to test the hypothesis. The findings indicate that the CEO's optimism, humility, and narcissism all had a positive effect on firm innovation. The consequences are that innovation in financial institutions is increasing when CEOs are optimistic, humble and narcissistic. The results suggest that, in order for financial institutions to be innovative, they need to have the CEOs who are optimistic and who epitomize visionary objectives to be committed to innovation. Likewise, they should have CEOs who are humble enough to involve key stakeholders and a narcissistic CEO who can stand decisively for organizational change in the form of innovation. This study is important in understanding how the CEO's personality contributes to firm innovation.